Indirect Flow-Injection Spectrophotometric Determination of Some -Lactam Antibiotics - Al-Momani, Idrees; Thalji, Mohammad (Jordan Journal of Pharmaceutical Sciences, 2021)
A simple and sensitive indirect spectrophotometric flow injection analysis (FIA) method for the determination of cefixime (CF), ceftriaxone (CFTR), cefotaxime (CFX) and cefuroxime (CFU) in pharmaceutical formulations and biological fluids has been suggested. Drugs under investigation are firstly oxidized by excess N-bromosuccinimide (NBS) in acidic medium, then the excess NBS is reacted with Rhodamine B (RB) to bleach its pinkish red color. Chemical variables and flow injection variables are all optimized to enhance reproducibility and sensitivity. The suggested procedure followed Beer’s law over concentration ranges of 5 – 30 μg.ml-1 for all tested drugs. The method is successfully applied to the determinations of the drugs under investigation in different pharmaceutical preparations. Results obtained by the suggested method were in excellent agreement with those obtained by the formal HPLC methods.